Surgical skills of specialty trainees in emergency gynaecological laparoscopic procedures: A national UK survey. (July 2014) - Christopoulos, G.; Kelly, T.; Lavery, S.; Trew, G.
Abstract A web-based survey was e-mailed to all specialty trainees ST Years 3–7 (n = 773) to assess their competence in emergency laparoscopic procedures. The trainees were asked about their competence level in a diagnostic laparoscopy; a salpingectomy; a salpingotomy; and an oophorectomy/cystectomy for adnexal torsion. Subsequently, they were asked how they would manage a tubal ectopic pregnancy with contralateral tubal disease. We received 202 responses (26%) and of these: 79% of trainees can perform a diagnostic laparoscopy independently; 32% can perform a salpingectomy and 12% can perform a salpingotomy independently; 14% can manage an adnexal torsion without supervision.